IgG1 versus IgG3: influence of antibody-specificity and allotypic variance on virus neutralization efficacy - Kallolimath, Somanath; Sun, Lin; Palt, Roman; Föderl-Höbenreich, Esther; Hermle, Antonia; Voss, Leonie; Kleim, Marina; Nimmerjahn, Falk; Gach, Johannes S.; Hitchcock, Lauren; Chen, Qiang; Melnik, Stanislav; et al. (Frontiers in Immunology, 2024)
Despite the unique advantages of IgG3 over other IgG subclasses, such as mediating enhanced effector functions and increased flexibility in antigen binding due to a long hinge region, the therapeutic potential of IgG3 remains largely unexplored. This may be attributed to difficulties in recombinant expression and the reduced plasma half-life of most IgG3 allotypes. Here, we report plant expression of two SARS-CoV-2 neutralizing monoclonal antibodies (mAbs) that exhibit high (P5C3) and low (H4) antigen binding. P5C3 and H4-IgG1 mAbs were subclass-switched to IgG3 formats, designed for efficient production and increased PK values, carrying three allotypic variations, referred to as -WT, -H, and -KVH. A total of eight mAbs were produced in glycoengineered plants that synthesize fucose-free complex N-glycans with great homogeneity. Antigen, IgG-FcγR immune complex and complement binding studies demonstrated similar activities of all mAbs. In accordance, P5C3 Abs showed minor alterations in SARS-CoV-2 neutralization (NT) and antibodydependent cell-mediated virus inhibition (ADCVI). Clear functional differences were observed between H4 variants with superior ADCVI and NT potencies of H4 IgG3 H. Our comparative study demonstrates the production of an IgG3 variant carrying an Fc domain with equivalent or enhanced functions compared to IgG3-WT, but with the stability and PK values of IgG1. Our data also demonstrate that both allotypic variability and antibody specificity are important for fine-tuning of activities, an important information for the development of future therapeutics.